Adapting to an Unconventional Use of a Chat Environment in Workplace Training - Piia Mikkola; Esa Lehtinen; Riikka Nissi (Social Interaction)
This article investigates how a digital chat tool is used during a face-to-face workshop where it is projected on a screen for everyone to see. Importantly, the chat is not used as an interactional tool but rather, in an unconventional way, as an archive for photographs the participants have taken for a workshop task. Thus, in order to discuss the photographs, the facilitator using the computer needs to navigate in the digital space with the help of the photographer to find each photograph. Drawing on multimodal conversation analysis and the concept of affordance, we show how the participants, during the course of the workshop, adapt to the task-relevant affordances and learn to conduct the navigation in an increasingly collaborative fashion.